Antitrust Enforcement in the United States: Market Structure Versus Market Conduct - William H. Barrett; Manley R. Irwin (Washington University Law Quarterly, 1974)
First, we will review the basic tenets of the two underlying “schools” of antitrust policy, the structuralist and conduct⁄performance Schools. Secondly, we will survey the records of both private and public antitrust enforcement and review the advantages and disadvantages of each. Thirdly, we will argue that an alternative to present antitrust enforcement responsibilities and practices is necessary, and suggest that establishing a Federal Industrial Reorganization Commission may be the only effective means to ensure that economic competition, diversity, and dynamism prosper and prevail in the decades ahead. Such a solution is currently before Congress in the proposed Industrial Reorganization Act (Hart Bill).
Keywords: Antitrust law; Economics; Sherman Act